A study on factors influence of free relationship among final year students in UiTM Kedah / Norfaezah Hashim - Hashim, Norfaezah (Faculty of Information Management, 2010)
Free relationship is one of the social problems. The independents variables are the factor influences of free relationship that includes peer, family background, trend and Information Communication Technology (ICT). This study intends to identify the social problem and at the same time it can find the factor influences of free relationship problem. The main point of data collected is to know the factor that make the free relationship problem and the kind of relationship that entered among final year’s students in UiTM Kedah for all faculties.